World Workshop on Oral Medicine VII: What participants perceive as important. (29th May 2019) - Brailo, Vlaho; McKnight, Patrick; Kerr, Alexander R.; Lodi, Giovanni; Lockhart, Peter B.
Abstract: Our objective was to identify which aspects of World Workshop on Oral Medicine (WWOM) participation were perceived as significant for participants' professional development. Online survey was sent to previous WWOM participants. Qualitative analysis of participants' responses to an open‐ended question was performed. Fifty‐two WWOM participants responded. Nearly three quarters of respondents (72.3%) felt that participation in the WWOM helped their career. A high percentage of respondents (67.3%) provided answers that fell under the domains of international collaboration, followed by personal academic benefits (48%). Overall, the results indicate that WWOM participation played an important role in individual's professional development. We identified aspects of WWOM involvement that the participants perceived as important. This information will be used for the development of an objective instrument for measuring impact of WWOM on participant's professional path.